Residência multiprofissional em saúde coletiva sob a ótica pedagógica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Introduction: Residencies professional health area are lato sensu Graduate Programs, in the teaching-service modality, in the multiprofessional and uniprofessional categories. Objective: To analyze the pedagogical process in a Multiprofessional Residence Program in Collective Health in a municipality in the south of Brazil. Method: This is a participative evaluative research of the case study type, with a qualitative and quantitative approach, carried out in a multiprofessional residence program in public health. The research subjects were the preceptors and residents. The collection took place in the period from 2019 to 2020. It was used as an instrument for collecting quantitative data, the Assessment and Knowledge Scale adapted and composed of the following axes: 1) institutional infrastructure for the development of the program; 2) organization and the pedagogical project; 3) qualification of the faculty, coordinators, preceptors and tutors; 4) integration with the policies of the Unified Health System and 5) incorporation of new technologies and innovations in service and teaching practices. The qualitative approach was carried out by applying a questionnaire containing three open questions that were answered in writing, related to the considerations regarding the Multiprofessional Residence in Public Health, the similarities and differences between the multiprofessional residency and previous training experiences and learning and teaching at the residence. Descriptive statistical measures and comparisons for variables were used. The level of significance adopted was 5%. Qualitative data were analyzed using the Collective Subject Discourse technique. Results: The study subjects were preceptors (n = 29) and residents (n = 57). For the total number of participants, on a scale with scores from 0 to 100, Axis 1 had the worst assessment (51.1 + 18.6) and Axis 5 (76.2 + 19.1) the best. In comparison, Axis 1 (Preceptor 59.5 + 14.5 vs Resident 46.8 + 19.1; p <0.01), Axis 2 (Preceptor 75.0 + 12.9 vs Resident 66, showed significant differences). 3 + 14.0; p <0.01) and Axis 4 (Preceptor 77.6 + 19.4 vs Resident 69.0 + 17.3; p = 0.02). Axes 3 and 5 did not show significant differences between the two groups. Conclusion: In general, the preceptors evaluated the Multiprofessional Residency Program in Collective Health better, when compared to the residents. The Collective Subject Discourse highlighted the categories: potential and weaknesses of the program, differences in residency in relation to previous training experiences and considerations regarding teaching and learning in residence.
Keywords: Educação em Saúde; Formação Profissional; Saúde Coletiva; health education; vocational training; public healt; CNPQ::CIENCIAS DA SAUDE